Apology strategies in Jordanian Arabic - Banikalef, Ala’Eddin Abdullah Ahmed; Maros, Marlyna; Aladdin, Ashinida; Al-natour, Mouad (Penerbit UKM, 2015)
Most apology studies in the Jordanian context have investigated apologies based on a corpus of elicited data. Rarely have apologies been observed in the natural data; nor have the contextual factors that obligated these apologies been considered. This study is based on a corpus of 1100 naturally occurring apology events, collected through an ethnographic observation. Semi-structured interview was also used to examine the influence of contextual factors (social status, social distance, and severity of offence) on the choice of apology strategies. The respondents for this study were selected via convenient sampling. The naturally occurring apologies were coded using a modified version of the apology strategy typology outlined by Olshtain and Cohen (1983). There are series of findings that are worth noting; the first is that, acknowledging responsibility was the most common apology strategy in Jordanian Arabic. Second, acknowledging responsibility and swearing by God’s name, formed the most frequent combination of apology strategies in this language. Third, another strategy that was high on the percentage of occurrence and deserving discussion was the nonapology strategies. Fourth, the selections of apology strategies were influenced by social status more than the degree of the severity of the offence or the social distance. Last but not least, new culture-specific apology strategies were detected in the corpus and elaborated in the paper. The findings of the study will assist material developers in preparing for resource books or modules for teaching and training of language and cultural awareness. The findings can also be used to raise the awareness about the sociocultural rules that govern the use of language functions.